The impact of the UK government's tax, welfare and minimum wage reforms in Wales - James Browne (Institute for Fiscal Studies (IFS), 2015)
The UK government's proposed package of tax and benefit changes (those announced in fiscal events up to and including the July Budget) to be introduced between 2015-16 and 2019-20 will reduce the incomes of households in Wales by 459 a year on average (an aggregate loss of around 600 million). This is roughly the same in cash terms as the average for the UK as a whole, but since average incomes in Wales are below the UK average, this represents a larger percentage of net income. Reductions in income will not be evenly felt across different types of household. Lower-income households, particularly those with children will lose considerably more than this amount on average. Better-off households and pensioners will be less affected or even gain from these changes. Low-income working households lose roughly the same as low-income non-working households on average. However, this will change following the introduction of universal credit as universal credit benefits some working households, in particular single-earner couples, but reduces the incomes of some non-working households. Cuts to out-of-work benefits will modestly strengthen work incentives onaverage. Two summary measures of the incentives for people to be in paid work, the participation tax rate and the replacement rate, both fall by 2.2 percentage points (ppts) on average, the average participation tax rate from 36.1% to 34.0% and the average replacement rate from 55.5% to 53.3%. Given the scale of the benefit cuts, this is perhaps a smaller impact than one might have expected. A key explanation for the limited effect these policies have on work incentives is the significant planned cuts to in-work support. Indeed, benefit changes other than universal credit increase average participation tax rates for those groups who are more likely to receive in-work support, namely lone parents and those whose partner is not in paid work. Universal credit also strengthens work incentives on average, but in many ways has the opposite effect to other benefit changes, as it particularly strengthens work incentives for those who have a partner who is not in paid work. However,neither universal credit nor other benefit changes significantly strengthen work incentives for lone parents. Tax and benefit changes to be introduced over the next four years on average strengthen the incentive for those in paid work to increase their earnings. [...]
Keywords: 330